Molecular epidemiology of co‐infection with hepatitis B virus and human immunodeficiency virus (HIV) among adult patients in Harare, Zimbabwe. Issue 2 (9th August 2016) - Baudi, Ian; Iijima, Sayuki; Chin'ombe, Nyasha; Mtapuri‐Zinyowera, Sekesai; Murakami, Shuko; Isogawa, Masanori; Hachiya, Atsuko; Iwatani, Yasumasa; Tanaka, Yasuhito
Abstract : The objective of this study was to determine the prevalence of co‐infection with hepatitis B virus (HBV) and human immunodeficiency virus (HIV) and the genetic characteristics of both viruses among pre‐HIV‐treatment patients in Harare, Zimbabwe. This cross‐sectional survey involved 176 remnant plasma samples collected from consenting HIV patients (median age 35 [18–74]) between June and September 2014. HBV seromarkers were determined by high‐sensitivity chemiluminescence assays. Molecular evolutionary analyses were conducted on the basal core promoter/precore (BCP/PC) and S regions of HBV, as well as part of the HIV pol region. Of the 176 participants (65.7% female), 19 (10.8%) were positive for HBsAg (median 0.033 IU/ml (IQR 0.01–415). The HBsAg incidence was higher in men than women ( P = 0.009). HBsAg‐positive subjects had lower median CD4 counts ( P = 0.016). HBV DNA was detectable in 12 HBsAg‐positive samples (median 3.36 log cp/ml (2.86–4.51), seven being amplified and sequenced. All isolates were subgenotype A1 without HBV drug resistance mutations but each had at least one BCP/PC mutation. PreS deletion mutants and small S antigen variants M133I/T and D144G were identified. Of the 164 HIV isolates successfully genotyped, 163 (99.4%) were HIV‐1 subtype C and only one was HIV‐1 subtype F1. Sixteen (9.8%) had at least one drug resistance mutation, predominantly non‐nucleoside reverse transcriptase inhibitor‐related mutations, observed mostly among female participants. This study shows that co‐infection with HBV is present among HIV patients enrolling into HIV care in Zimbabwe, suggesting that HBV screening and monitoring programmes be strengthened in this context. J. Med. Virol. 89:257–266, 2017 . © 2016 Wiley Periodicals, Inc.